Chemical composition of Essential Oils of Four Scandix Species from Different Parts: A Chemotaxonomic Approach - Demirpolat, Azize; Dogan, Gulden; Bagci, Eyup (Taylor & Francis Ltd, 2018)
The chemical composition of the essential oils of dried aerial parts of four Scandix species; Scandix aucheri Boiss., Scandix pecten-veneris L. (aerial parts and fruit), Scandix macrorhyncha C.A. Mey. and Scandix balansae Reuter ex Boiss. was analyzed by using GC and GC-MS. The essential oil yield of S. aucheri showed 37 components , which comprised of 98 % of the total essential oil and identified 16 constituents in fruit and 18 constituents in aerial part of S. pecten veneris. 10 compounds were identified which comprised 89.6 % of the total essential oil from S. macrorhyncha, and 33 constituents were identified in S. balansae and comprised 83.5 % in total essential oil. The main compounds were determined as germacrene D (22.3 %), spathulenol (11.5 %), in S. aucheri; n-hexadecanoic acids (Palmitic) (28.2 %), spathulenol (19.6 %) in (aerial parts)-n-hexadecanoic acids (27.7 %), octadecanoic acids (6.7 %) in fruit from S. pecten veneris; n-hexadecanoic acids (31.5 %), 1-heptadecanol (25.2 %), in S. macrorhyncha, 9,12-octadecanoic acids (Linoleic) (26.6 %), 9-octadecanoic acids (oleic) (15.3 %), n-hexadecanoic acids (10.7 %) in S. balansae. Fatty acid, sesquiterpene and saturated hydrocarbons were determined as significant compounds for the characterization of Scandix species essential oil. The results were discussed in view of natural products and chemotaxonomy.
Keywords: Scandix; essential oil; chemotaxonomy; GC-MS; n-hexadecanoic acids (Palmitic)